Assessing the effect of Covid 19 on selective SMEs in South Africa Jacques Vassard - Vassard, Jacques (University of the Witwatersrand, Johannesburg, 2024)
The COVID-19 pandemic has brought forth a myriad of challenges for small and medium-sized enterprises (SMEs), particularly in South Africa. These challenges include financial instability, fluctuations in market demand, supply chain disruptions, government policy changes, and consumer behaviour modifications. This study aims to delve into these unique circumstances and challenges faced by SMEs in South Africa during this unprecedented global health crisis. For my study, I will be analysing the factors that affect the performance of Small and Medium Enterprises (SMEs) in South Africa during the COVID-19 pandemic. I will use a qualitative research approach to examine the impact of COVID-19 on the performance of fifteen SMEs in South Africa. Qualitative research can provide valuable insights into the challenges faced by these enterprises. This research method focuses on understanding SMEs' experiences, beliefs, and personal interpretations, allowing for a thorough investigation of the subject. Based on the data collected, 60% of these businesses experienced a negative impact on their revenue generation ability. The lockdown restrictions compelled SMEs to cease operations, resulting in significant losses. Among the SMEs, 47% reported declining demand for their products or services during the pandemic. Additionally, 47% of the SMEs experienced supply chain problems. Furthermore, 53% of SMEs reported that the policies put in place had caused harm to their businesses. The latest factor studied was the purchasing behaviour of small and medium-sized enterprises (SMEs) and how the COVID-19 pandemic affected their customers' habits. 40% of these SMEs reported decreased client purchases during this period. The study underscores the resilience and adaptability of small and medium-sized enterprises (SMEs) in South Africa amid the multitude of challenges posed by the COVID-19 pandemic. The insights derived from this qualitative research highlight the critical need for targeted support and interventions to strengthen the sustainability and growth of SMEs in the face of such unprecedented disruptions
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Covid 19; SMEs in South Africa; UCTD; SDG-8: Decent work and economic growth